Analysis of the Influence of Infrastructure Development, Poverty, and Education on Economic Growth in Mataram City 2014 – 2023 - Sari, Desinta Arum; Salmah, Emi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Economic growth is strongly influenced by infrastructure, poverty, and education. Good infrastructure accelerates the distribution of goods, services, and labor, which increases productivity and encourages investment. High poverty hinders economic growth because it limits people's access to essential resources such as education and health, thereby reducing productive participation. Quality education improves workforce skills, encourages innovation, and strengthens competitiveness, all of which contribute to sustainable and inclusive economic growth. The goal of this study is to evaluate how infrastructural development, poverty, and education affect economic growth in Mataram City. This study employed quantitative research. The data utilized in this study are secondary data acquired from BPS, and the analysis technique employed is multiple regression analysis to assess the association between variables, with data processed using the SPSS program. The results of the study show that infrastructure development, poverty and education have a positive effect on economic growth in Mataram City in 2014 – 2023.